Perempuan Gen X: Literasi Digital di Instagram Vs Facebook - Maria Yuliastuti (Fakultas Ilmu Komunikasi UKWMS, 2023)
ABSTRACT The onslaught of social media has dominated and has become even more so during the Covid-19 pandemic. Women as spearheads of family resilience have a tough task during a pandemic. Mastery and use of social media for women is very important, especially Gen X women make a major contribution in educating children and also supporting family economic activities. The Republic of Indonesia Catholic Women's Group (WKRI) was the subject of this study. This study uses a quantitative approach to the survey method. It was found that the literacy ability of the WKRI group on the Facebook feature was high and vice versa on the Instagram feature. Some of the parts that influence them are age, education, profession, and the amount of expenses of the respondents. The duration of access does not affect literacy skills. Gen X women are still reluctant to switch to Instagram and are still comfortable using Facebook. Even though the duration of accessing Instagram and Facebook is almost the same, it doesn't guarantee the mastery of both features. ABSTRAKGempuran media sosial telah mendominasi dan semakin menjadi pada masa pandemi covid-19. Perempuan sebagai ujung tombak ketahanan keluarga memiliki tugas yang berat saat pandemi. Penguasaan dan pemanfaatan media sosial bagi perempuan sangatlah penting, terlebih perempuan Gen X berkontribusi besar dalam mendidik anak dan juga menopang kegiatan ekonomi keluarga. Kelompok Wanita Katolik Republik Indonesia (WKRI) yang didominasi oleh perempuan Gen X menjadi subjek dalam penelitian ini. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Didapatkan temuan bahwa kemampuan literasi kelompok WKRI pada fitur Facebook adalah tinggi dan pada fitur Instagram sebaliknya. Beberapa bagian yang mempengaruhi diantaranya adalah usia, pendidikan, profesi, dan besarnya pengeluaran dari responden. Lama durasi akses tidak mempengaruhi kemampuan literasi. Perempuan Gen X masih enggan untuk beralih ke Instagram dan masih nyaman menggunakan Facebook. Walaupun durasi dalam mengakses Instagram dan Facebook hampir sama, ternyata tidak menjamin kemampuan penguasaan fitur keduanya.